Role of Uttarabasti in Neurogenic Urinary Incontinence (International Journal of Ayurveda and Pharma Research, 2024)
Neurogenic bladder refers to dysfunction of the urinary bladder arising from internal or external trauma, disease, or injury of the central, autonomic or somatic nervous system in the control of micturition. Depending on the nerves involved and the nature of the damage, bladder becomes either overactive or underactive and this usually presents clinically as urinary incontinence or retention of urine. Urinary Incontinence (UI) is a hygienic problem and is one of the troublesome, important cause of morbidity and impairment of quality of life, in both men and women. It may lead to recurrent UTI and ascending infections which affect the functioning of kidney. Deranged function of Vatadosha especially Apanavata along with Pranavata and Vyanavata are the main culprits of neurogenic bladder. Vitiated Doshas cause Mootravahasrotodushti and Atipravritti of mootra. This case study discusses the effect of Mootramarga uttarabasti in reducing the signs and symptoms of neurogenic urinary incontinence and thereby improving the quality of life. A 66 year old male patient was admitted with weakness in left upper and lower limbs, slurred speech, and difficulty in controlling micturition since 5 months. He was a diagnosed case of stroke on the basis of a brain computed tomography scan. During the course of management, Uttarabasti was administered for 8 days with Dhanwantarataila and Balamoolakashaya alternatively. The intervention resulted in reducing the symptoms of neurogenic urinary incontinence as evidenced by the reduction in ICIQ-UI -SF score. It was observed that the overall impact of the disease was reduced and quality of life improved with the help of King’s Health Questionnaire (KHQ).